Defiance of Implementing Distance Education in the Education System - Rodríguez Zavala, Luisa (2021)
This article aims to explore the implementation of distance education in Peru. To this end, we propose to make a theoretical approach to the concept of distance education. This is where two concepts emerge that will be key to the implementation of distance learning: virtuality and technologies. Both are vital for distance learning. However, considering certain structural, social and economic aspects, it will be appreciated that, although distance education requires certain minimum socio-economic conditions in order to be viable, its implementation in Peru has omitted this, implementing distance education without considering them; this has caused many students at primary, secondary and university levels to be forced to leave their studies due to lack of financial resources. Faced with this, the need for an inclusive distance education emerges; therefore, methodologically we will make a theoretical and epistemological review of the main existing paradigms within distance education and virtuality. Methodologically it is a longitudinal study that covers the years 2000 - 2020. Therefore, the work will be supported in an exploratory methodology.